Foot Alignment Profile in Injured Professional Basketball and Football Athletes. Issue 3 (14th September 2018) - de Cesar Netto, Cesar; Bernasconi, Alessio; Roberts, Lauren; Lintz, Francois; Richter, Martinus; O'Malley, Martin
Category: Sports Introduction/Purpose: Adequate evaluation of foot and ankle problems in elite athletes is paramount for planning the correct treatment, predicting clinical prognosis and supporting decision making. A complete physical examination that includes the assessment of foot alignment during weightbearing is mandatory. The three-dimensional evaluation provided by weightbearing CT imaging (WBCT) represent an important diagnostic tool for foot and ankle surgeons when dealing with these extremely physically active patients. The purpose of this study was to assess different WBCT measurements of hindfoot and forefoot alignment in injured high-level football and basketball players. We hypothesized that specific patterns of hindfoot alignment and height of the longitudinal arch of the foot could be identified. Methods: In this single center retrospective comparative study, 80 professional male athletes - 47 basketball and 33 American football players from College, NBA and NFL leagues - that underwent WBCT as part of the clinical investigation for different injuries of the foot and ankle were included in the study. WBCTs images were evaluated by a blinded board-certified foot and ankle orthopedic surgeon. Multiple measurements used for assessment of hindfoot valgus and longitudinal arch height were assessed and included: foot and ankle offset (%), calcaneal offset (mm), hindfoot alignment angle (°), navicular-floor distance (mm), medial cuneiform-floor distance (mm), forefoot arch angle (°), inferior talar-superior talar angle (°), and subtalar horizontal angle (°). An unpaired Student's t test was performed to evaluate any differences in the measurements when comparing professional basketball and football patients. P-values less than 0.05 were considered significant. Results: A summary of demographic characteristics and each measurement's distributions and standard deviations, as well as p-values for the analysis between groups, is given in table 1. No significant differences were found between basketball and American football elite athletes when comparing the mean values of measurements evaluated (mean differences): foot and ankle offset (0.26%), calcaneal offset (0.58 mm), hindfoot alignment angle (0.73°), navicular-floor (0.35 mm) and medical cuneiform-floor distances (0.38 mm), forefoot arch angle (0.74°), inferior talar–superior talar angle (0.83°) and subtalar horizontal angle (0.1°). Conclusion: Although we did not find significant differences in foot alignment when comparing basketball and American football professional athletes, the results of our study highlight some of the important foot alignment parameters and establish distributions in an extreme but important population. Further studies correlating foot alignment with the incidence of some of the most common pathologies diagnosed in elite athletes, such as the ones reported in our study, can help in the understanding and prevention of those injuries.